Event and strategy analytics - DONG, Jin Song (Institutional Knowledge at Singapore Management University, 2015)
Model checking has been pervasive and successful in finding bugs in hardware and software systems, including real-time and probabilistic systems. Applying model checking to decision making is relative new and has an excellent potential to be compliment to data analytics and other Artificial Intelligent (AI) or Operational Research (OR) based decision making techniques. Our last 8 years research has focused on the development of PAT (Process Analysis Toolkit) [18] which supports modelling languages that combine the expressiveness of event, state, time and probability based modeling techniques to which model checking can be directly applied. The next direction for PAT is to move from verification to analytics, we call it “Event Analytics” with a special focus on “Strategy Analytics”.